2022
DOI: 10.2147/ccide.s364814
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life and Supporting Structures in Implant Retained Mandibular Overdenture: A 5-Year Cohort Study

Abstract: Aim To assess oral health-related quality of life (OHRQoL), marginal bone loss (MBL), and changes in soft tissue including probing pocket depth and implant stability in 2 implants retained mandibular overdentures during 5 years follow-up periods. Methods Forty completely edentulous patients with age 51–64 years were recruited for that longitudinal cohort study. Complete dentures were performed for all participants. Two implants (3.6 × 11.5 mm) were installed in the cani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This fact was the foundation of choosing this line of treatment in this RCT being profoundly supported in literature. (4,7,12) According to the McGill consensus, the use of two conventional length (8 mm or more) implants is considered the gold standard for implant-retained mandibular overdenture. (19) However, a common problem presented in edentulous patients is the mandibular ridge atrophy which interferes with straight foreword implant placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact was the foundation of choosing this line of treatment in this RCT being profoundly supported in literature. (4,7,12) According to the McGill consensus, the use of two conventional length (8 mm or more) implants is considered the gold standard for implant-retained mandibular overdenture. (19) However, a common problem presented in edentulous patients is the mandibular ridge atrophy which interferes with straight foreword implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Implant-assisted overdentures have become an increasingly accepted alternative for oral rehabilitation of edentulous patients, especially in cases of mandibular arches. (4) Despite the solid foundation of using implants for prosthetic restoration of edentulous patients, the presence of a sufficient volume of healthy bone remains the most important prerequisite for implant success which is not the case with severe mandibular residual ridge atrophy. (5) Pre-prosthetically, different treatment approaches can be used to enable implants to be placed in atrophied ridges.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that OHIP scores and implant stability improved from 1 year after the start of loading until 4 years after the start of loading, but then worsened in the fifth year of follow‐up. These reduced scores may have been due to the need for relining, repair or correction of occlusal problems (Abd El Rahim & Ashour, 2022). Our finding that OHIP scores continued to improve over a 9‐year period may be due to the easy‐to‐use retention type and relatively manageable complications.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported a positive long-term effect of mandibular two implants retained overdentures on OHRQoL, MBL, probing pocket depth, and implant stability. 29 …”
Section: Discussionmentioning
confidence: 99%
“…This study reported a positive long-term effect of mandibular two implants retained overdentures on OHRQoL, MBL, probing pocket depth, and implant stability. 29 The second null hypothesis was that no differences between platform switched (GI) and matched implants (GII) retained mandibular overdentures in their influences on MBL or the probing pocket depth after 6 years follow-up period. That hypothesis was accepted.…”
mentioning
confidence: 99%